Bone microstructure supports a Mesozoic origin for a semiaquatic burrowing lifestyle in monotremes (Mammalia) - Suzanne J. Hand; Laura A. B. Wilson; Camilo López-Aguirre; Alexandra Houssaye; Michael Archer; Joseph J. Bevitt; Alistair R. Evans; Amalia Y. Halim; Tzong Hung; Thomas H. Rich; Patricia Vickers-Rich; Robin M. D. Beck (Proceedings of the National Academy of Sciences, 2025)
The platypus and four echidna species are the only living egg-laying mammals and the sole extant representatives of Order Monotremata. The platypus and echidnas are very disparate both morphologically and ecologically: The platypus is a specialized semiaquatic burrowing form that forages for freshwater invertebrates, whereas echidnas are fully terrestrial and adapted for feeding on social insects and earthworms. It has been proposed that echidnas evolved from a semiaquatic, platypus-like ancestor, but fossil evidence for such a profound evolutionary transformation has been lacking, and this hypothesis remains controversial. Here, we present original data about the Early Cretaceous (108 to 103 Ma) Australian mammal Kryoryctes cadburyi , currently only known from a single humerus, that provides key information relating to this question. Phylogenetic analysis of a 536-character morphological matrix of mammaliaforms places Kryoryctes as a stem-monotreme. Three-dimensional whole bone comparisons show that the overall shape of the humerus is more similar to that of echidnas than the platypus, but analysis of microstructure reveals specializations found in semiaquatic mammals, including a particularly thick cortex and a highly reduced medullary cavity, present in the platypus but absent in echidnas. The evidence suggests Kryoryctes was a semiaquatic burrower, indicating that monotremes first evolved an amphibious lifestyle in the Mesozoic, and providing support for the hypothesis that this is ancestral for living monotremes as a whole. The lineage leading to the modern platypus appears to have been characterized by extremely long term (>100 My) niche conservatism, with echidnas representing a much later reversion to a fully terrestrial lifestyle.